Intercalibration of AMSR2 NASA Team 2 Algorithm Sea Ice Concentrations With AMSR-E Slow Rotation Data - Meier, Walter N.; Ivanoff, Alvro (IEEE journal of selected topics in applied earth observations and remote sensing, 2017)
Sea ice estimates from AMSR2 are intercalibrated with AMSR-E fields through a two-step process. First, slow rotation 2 r/min AMSR-E data is used to derive regression equations from colocated pairs of AMSR2 and AMSR-E brightness temperatures (T b s). The regression equations are used to modify AMSR2 T b s into AMSR-E equivalent Tbs that are then input into the NASA Team 2 (NT2) sea ice concentration algorithm used for the AMSR-E standard products. The regressed T b s result in changes in sea ice concentration of a few percent compared to using the original un-regressed AMSR2 T b s. Next, sea ice estimates from the F17 SSMIS sensor are used as a bridge to compare AMSR-E total sea ice extent estimates in 2010 with AMSR2 total sea ice extent estimates in 2013. Based on this comparison, a further adjustment is made to a weather filter threshold used in the NT2 algorithm to minimize the total extent bias between AMSR2 and AMSR-E using a double-differencing approach. The adjustments reduced apparent bias with AMSR-E from ~200 000 km 2 for the original unmodified AMSR2 T b s to -700 and 4700 km 2 for the Arctic and Antarctic, respectively. These differences are within the range of previous passive microwave sea ice intercalibrations. The adjusted AMSR2 sea ice fields provide a nearly 15-year time series of sea ice change; depending on the lifetime of AMSR2 and possible follow-on sensors, AMSR2 has the potential to be part of a multidecadal record of sea ice change.